Jamalat al-Khat al-Arabi wal-Takwinat al-Khatiyah fi Kiswat al-Ka'bah al-Musharrafah: Dirasah Faniyah Tahliliyah - Duaa Mohammed Alashari (UIN Raden Mas Said Surakarta, 2023)
The covering of the Kaaba possesses aesthetic values ​​and dimensions that are embodied through the artistic composition of Arabic calligraphy, and this artistic composition is an exquisite aesthetic artistic issue that evokes admiration, appreciation, and reverence. Therefore, this study aims to reveal the aesthetic characteristics and systems with fine artistic values ​​for Arabic calligraphy and the linear formations embodied in the honorable dress of the Kaaba according to a methodological perspective and an artistic vision. The study found that the covering of the Kaaba, with its Arabic calligraphy and calligraphic formations, expresses the originality of the Islamic nation and the aesthetic dimension inherent within the scope of Islamic art. And that the Arabic calligraphy is characterized by aesthetic characteristics that make it a decorative element as it contains many artistic and aesthetic values, and in particular the complex clear third line. The study also found that the totality of the calligraphic formations was formulated in an eloquent and aesthetic artistic style that added to the beauty of the verbal meaning by the aesthetics of the linear composition, and in this, the visual rhetoric and the aesthetics of the textual structure were manifested based on the ability of Arabic letters according to a wonderful aesthetic style based on the characteristics and systems of the linear composition.